2019
DOI: 10.3390/coatings9020135
|View full text |Cite
|
Sign up to set email alerts
|

Corrosiveness of Palm Biodiesel in Gray Cast Iron Coated by Thermoreactive Diffusion Vanadium Carbide (VC) Coating

Abstract: Palm biodiesel is a currently used biofuel, principally as an additive or substitute of diesel fuel in vehicular internal combustion engines. In the present work, vanadium carbide (VC) coatings were deposited on gray cast iron (GCI) using the thermoreactive diffusion process (TRD) to evaluate the corrosiveness of palm biodiesel and compare it with gray cast iron corrosion behavior. VC coated and uncoated gray cast iron samples were tested by immersion corrosion tests (291 K and 313 K), cyclic oxidation test (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As we all know, coating is an important way to protect metals from corrosion. Some researchers reached the conclusion that vanadium carbide coating protects gray cast iron against corrosion by biodiesel [48]. Similarly, other researchers drew the conclusion that NbC coatings on gray iron provide protection against corrosion by palm biodiesel.…”
Section: Corrosion Study Of Single Fuelsmentioning
confidence: 99%
“…As we all know, coating is an important way to protect metals from corrosion. Some researchers reached the conclusion that vanadium carbide coating protects gray cast iron against corrosion by biodiesel [48]. Similarly, other researchers drew the conclusion that NbC coatings on gray iron provide protection against corrosion by palm biodiesel.…”
Section: Corrosion Study Of Single Fuelsmentioning
confidence: 99%
“…The anti-corrosive nature of petroleum diesel decreases by increasing the biodiesel concentration in the BDBFs, mostly due to fostering microorganism activities in the biodiesel fuels [18]. Besides, researchers corroborated that the BDBFs reported more corrosive than the petroleum diesel on uncoated gray cast iron [19], and AA 3003 aluminum meal [20], mostly due to a marked increase in water, total acidity, electrical conductivity, density, and viscosity so on of the BDBF as compared to the petroleum diesel after immersion tests. From the electrochemical tests, the corrosionresistance of carbon steel was reported the highest (at least one order of magnitude) in comparison to Al as well as the Cu in biodiesel, and the Cu metal showed the lowest corrosion-resistant properties than carbon steel and Al metals in biodiesel [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers worldwide have focused on studying the corrosive nature of different biodiesels [12]. For example, the uses of vegetable [13], canola [14], sunflower [15], palm [16], and soybean [17] oil have been studied using different automotive materials. Rocabruno-Valdés et al [13] compared the corrosion characteristics of pure copper, aluminium, stainless steel, and carbon steel in canola biodiesel using electrochemical methods for 528 h. It was observed that stainless steel is more susceptible to petting corrosion, while the corrosion rate of carbon steel is highest, whereas copper showed the lowest corrosion rate.…”
Section: Introductionmentioning
confidence: 99%